Financial Analysis Of Giving Mung Bean Sprout Bark Flour In Rations On Income Of Bali Duck Farms - D, Wyandhana; Kayana, I G. N.; Suasta, I M. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This research was conducted with the aim to determine the effect of mung bean sprout bark flour in rations on the income of Bali duck farms. This research was carried out for 8 weeks and carried out in the laboratory of the Faculty of Animal Husbandry, Udayana University, Sesetan street, Denpasar. This study was conducted by comparing the financial impact of three treatments, namely: (P0) Unprotected ducks (as controls), (P1) Ducks given 6% mung bean sprouts bark flour and (P2) Duks given 12% mung bean sprouts bark flour. Each treatment was carried out 5 repetitions, each repetition using 3 ducks. The variables observed in this study were: Total costs, Total revenues, Net Benefit, Revenue and Cost Ratio (R / C), Profit Rate and BEP (Break Even Point). The results of this study show that the ducks treated with mung bean sprouts bark flour were 12% the most profitable. With the Net Benefit of Rp. 53,130 higher than (P0) Rp. 8.420 and (P1) 18,190. from Revenue and Costs Ratio (P2) obtained a value of 1.06 higher than (P0) 1.01 and (P1) 1.02. Profit Rate (P2) of 6.68% higher than P0 1.03% and P1 2.25%, BEP Rupiah (P2) Rp. 329,750, (P0) Rp.659,500 and (P1) Rp. 494,625 and BEP units (P2) as many as 6 units, (P0) as many as 12 units and (P1) as many as 10 units. It was concluded that the treatment (P2) was the most profitable compared to other treatments.   Keywords : Duck, financial analysis, mung bean sprouts bark flour.